Maternal-offspring behavior of Guzerat beef cattle - Pires, Bianca Vilela; Freitas, Luara Afonso de; Silva, Gabriele Voltarei da; Mendonça, Gabriela Geraldi; Savegnago, Rodrigo Pelicioni; Lima, Maria Lúcia Pereira de; El Faro, Lenira; Cyrillo, Joslaine Noely dos Santos Gonçalves; Paz, Claudia Cristina Paro de (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the characteristics of the maternal-offspring behavior of Guzerat bovines (Bos indicus) and the influence of this behavior on herd losses. A total of 73 gestating cows (multiparous and primiparous) and their respective calves were evaluated for the following behavioral traits: contact period between cow and calf (CPCC), cow age at calving, teat conditions, calf vigor at birth, need for human assistance (HA), and calf mortality until weaning. The mean weight of calves at birth was 29.12 kg. Vigor at birth was observed in 61.64% of calves; however, 27.4% of the calves required human assistance. Calf vigor was influenced by the CPCC, and calves without vigor needed more time with their mothers. Calves with low weight at birth required HA, whereas calves from cows with intermediate-sized teats did not. The absence of vigor at birth increased the mortality rate. The traits age of cows and vigor of calves at birth influence both the need for human assistance to calves in their first hours of life and herd losses.